Maturação e aquisição de tolerância à dessecação de sementes de Annona emarginata (Shltdl.) H. Rainer - Corsato, Jaqueline Malagutti [UNESP] (2014)
The species Annona emarginata (Schltdl.) H. Rainer (araticum-de-terra-fria) is used as rootstock to Annonaceae family species. Suggest that the sowing of this species is carried out right after the seeds extraction, indicating that those are not tolerate to desiccation. The objective of the study was the maturation and the tolerance acquisition to desiccation of seeds of Annona emarginata correlating to the phases of seeds development, drying levels and storage with hormonal balance, soluble sugars, lipids, soluble proteins, LEA proteins and stress enzyme activity. The experiments were performed at the Laboratory of Physiology of Seed Germination of the Department of Botany, Institute of Biosciences - IB, Universidade Estadual Paulista Julio de Mesquita Filho (UNESP), Botucatu-SP. Were performed five collections and for each one of them the fruits at different stages were analyzed for size, coloring, total soluble solids percentage (° Brix), texture, weight, number and size of seeds. The seeds from those fruits at different stages of maturation were subjected to anatomical analyzes, determination of initial water content, drying curve, germination test, storage at low temperature (-5°C) and biochemical analyzes (total soluble sugars and total reducing sugars; total proteins; LEA proteins; total lipids; peroxidase activity; superoxide dismutase activity; lipoperoxide content quantification and hormone quantification). Tha data were submitted to the ANOVA (F test) and the averages compared by the Tukey test at 5% probability. We observed that seeds of Annona emarginata acquire tolerance to desiccation at 116 DAF, when the embryo is already developed with sucrose accumulation, LEA proteins, beyond low activity of stress enzymes (SOD, POD and Lipoperoxide levels). However, these seeds have reduced longevity, completely losing viability after 180 days of storage, regardless of the water content showed that, due to the damage caused by low ...